Synthesis and Preliminary Evaluation of a Novel 18F-Labeled 2-Nitroimidazole Derivative for Hypoxia Imaging - Lu, Jing; Zhang, Chi; Yang, Xi; Yao, Xi-Juan; Zhang, Qun; Sun, Xin-Chen (Frontiers in Oncology, 2021)
Objective: Hypoxia is prevalent in tumors and plays a pivotal role in resistance to chemoradiotherapy. 18F-MISO is currently the preferred choice of PET hypoxia tracers in clinical practice, but has severe disadvantages involving complex labeling methods and low efficient imaging due to lipophilicity. We aimed to design a novel nitroimidazole derivative labeled by 18F via a chelation technique to detect hypoxic regions and provide a basis for planning radiotherapy. Materials and Methods: First, we synthesized a 2-nitroimidazole precursor, 2-[4-(carboxymethyl)-7-[2-(2-(2-nitro-1H-imidazol-1-yl)acetamido)ethyl]-1,4,7-triazanonan-1-yl]acetic acid (NOTA-NI). For 18F-labeling, a 18F solution was reacted with a mixture of AlCl3 and NOTA-NI at pH 3.5 and 100 °C for 20 min, and the radiochemical purity and stability were evaluated. Biological behaviors of Al18F-NOTA-NI were analyzed by an uptake study in ECA109 normoxic and hypoxic cells, and a biodistribution study and microPET imaging in ECA109 xenografted mice. Results: Al18F-NOTA-NI required a straightforward and efficient labeling procedure compared with 18F-MISO. The uptake values were distinctly higher in hypoxic tumor cells. Animal studies revealed that the imaging agent was principally excreted via the kidneys. Due to hydrophilicity, the radioactivities in blood and muscle were decreased, and we could clearly distinguish xenografted tumors from para-carcinoma tissue by PET imaging. Conclusions: The nitroimidazole tracer Al18F-NOTA-NI steadily accumulated in hypoxic areas in tumors and was rapidly eliminated from normal tissue. It appears to be a promising candidate for hypoxia imaging with high sensitivity and resolution.